Pengaruh Corporate Governance Terhadap Nilai Perusahaan Yang Dimoderasi Oleh Investasi R&D (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di BEI) - SAJIWO TRI PRAKOSO, SAJIWO TRI PRAKOSO; , Dr. Syamsudin, MM; , Dra. Rina Trisnawati, Ak, M.Si, Ph.D (2017)
This study aimed to analyze the Influence of Corporate Governance on The Firm Value That Moderated By Investing R & D. These samples included 363 for manufacturing companies during the period 2012-2015. The sampling technique was conducted in purposive sampling. Corporate Governance is proxied by independent commissioners, institutional ownership, public ownership, R & D Investment proxy for R & D ,. While the dependent variable firm Value proxy for Tobinq. This analysis using MRA (Moderated Regression Analysis). The results showed that the independent commissioner did not significantly affect the firm value, to institutional ownership, public ownership and investment R & D has an influence on the firm value. While the mediator that R & D investment can not Moderated public ownership and firm value, to institutional ownership and independent directors on the firm value can be mediated by the R & D investment. Keywords: Corporate Governance, Investment R & D, Firm Value.